Clinicopathologic diagnostic criteria of an enigmatic entity: Proliferative verrucous leukoplakia - Ramnarayan Belur Krishna Prasad; Prathima Mallappa Maligi; Smitha Thimappa; Shashi Ram (Journal of Indian Academy of Oral Medicine and Radiology, 2015)
Proliferative verrucous leukoplakia (PVL) is a rare, unique type of oral leukoplakia, which is enigmatic in etiology and behaves in a far more aggressive fashion than other forms of leukoplakia. Diagnosis is often late with the disease in an advanced stage when it is especially refractory to treatment. There are no definite criteria that dictate how extensive the leukoplakic changes should be, how many or which oral subsites should be involved, or how many recurrences should have occurred, in order to qualify for the diagnosis of PVL. The lack of definitive diagnostic criteria is the prime reason for PVL not being treated appropriately and in a timely fashion, thereby leading to the very concept of PVL being questioned. This article discusses the various clinicopathologic diagnostic criteria for this enigmatic entity and also reports a case of PVL in a 73-year-old female.